2023
DOI: 10.1039/d2ra08247k
|View full text |Cite
|
Sign up to set email alerts
|

On-line pre-column FRAP-based antioxidant reaction coupled with HPLC-DAD-TOF/MS for rapid screening of natural antioxidants from different parts of Polygonum viviparum

Abstract: Polygonum viviparum L. (PV) is a widely used resource plant with high medicinal, feeding and ecological values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Referencing previous methodologies [40], we weighed approximately 0.5 g of the sample powder three times, and placed each portion into a separate 15 mL centrifuge tube. To each tube, we added 5 mL of ultrapure water, 50% methanol, and anhydrous methanol, respectively.…”
Section: Offline Extraction Of Samplementioning
confidence: 99%
“…Referencing previous methodologies [40], we weighed approximately 0.5 g of the sample powder three times, and placed each portion into a separate 15 mL centrifuge tube. To each tube, we added 5 mL of ultrapure water, 50% methanol, and anhydrous methanol, respectively.…”
Section: Offline Extraction Of Samplementioning
confidence: 99%
“…Its rhizome is considered to be primarily responsible for its pharmacological properties (e.g., antipyretic, antidiarrheal, menstruation-regulating, and hemostasis effects), and it is also an important food source for the host larvae of Cordyceps sinensis [ 5 ]. It has high medicinal, feeding, and ecological value [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have identified volatile oils, organic acids, and sterols from B. vivipara via traditional methods. However, there are abundant primary and secondary metabolites in plants, which comprise only some of them [ 6 ]. Metabolomics technology is mainly used to identify functional secondary metabolites and metabolic pathways [ 7 ].…”
Section: Introductionmentioning
confidence: 99%